From Misbehaviour to Courtroom: Analyzing Malaysia’s Legal Approach to Children Beyond Parental Control - Syed Nong, Shariffah Nuridah Aishah; Ismail, Nazli; bin Mustaffa, Aminuddin; binti Bidin, Asiah; Abu Taher, Mohammad (Faculty of Law, Jambi University, 2025)
Youth misconduct such as truancy, running away from home, smoking, and staying out late remains a recurring concern in Malaysia where public alarm has been amplified by viral social media cases. Legally, such adolescents fall under the category of “children beyond control” in the Child Act 2001. Between 2017 and 2023, the Department of Social Welfare recorded 1,534 cases nationwide, 40 of which were from the state of Terengganu. Failure to address such behaviour risks escalating into delinquency and crime, highlighting the need for early intervention. This study aims to identify the most prevalent forms of uncontrollable behaviour in Terengganu, examine legal procedures and rehabilitation orders imposed by the Court For Children, and propose improvements to strengthen child welfare protection. Using a descriptive socio-legal methodology, qualitative data were collected through semi-structured interviews with magistrates, welfare officers and probation officers, supplemented by library research. Findings indicate the need for comprehensive intervention strategies to ensure protection, rehabilitation, and reintegration. The study contributes to scholarship and practice by aligning case management with the National Child Policy and the United Nations Convention on the Rights of the Child, while offering practical insights to improve the handling of children beyond control in Terengganu.